2008
DOI: 10.1002/art.24106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the early use of the anti–tumor necrosis factor adalimumab on the prevention of job loss in patients with early rheumatoid arthritis

Abstract: Objective. To compare work disability and job loss in early rheumatoid arthritis (RA) patients receiving adalimumab plus methotrexate (adalimumab ؉ MTX) versus MTX alone. Methods. In this multicenter, randomized, controlled trial, patients with RA for <2 years who had never taken MTX and who self-reported work impairment were randomized to adalimumab ؉ MTX or placebo ؉ MTX for 56 weeks. Primary outcome was job loss of any cause and/or imminent job loss at or after week 16. Secondary outcomes included disease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
15

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(88 citation statements)
references
References 20 publications
(22 reference statements)
3
70
0
15
Order By: Relevance
“…These data provide additional evidence of the superiority of combination treatment, which is known to lead to greater improvements in signs and symptoms of RA, functional disability, health-related quality of life, and slowing of radiographic progression than methotrexate alone (17,20). The findings complement recent studies with smaller populations and shorter study durations in which patients who received combination treatment had better work outcomes than patients who received methotrexate alone (25,26). The patterns of work outcomes for employed workers and homemakers were very similar in this study; combination treatment was superior to methotrexate for both absenteeism and presenteeism.…”
Section: Discussionsupporting
confidence: 84%
“…These data provide additional evidence of the superiority of combination treatment, which is known to lead to greater improvements in signs and symptoms of RA, functional disability, health-related quality of life, and slowing of radiographic progression than methotrexate alone (17,20). The findings complement recent studies with smaller populations and shorter study durations in which patients who received combination treatment had better work outcomes than patients who received methotrexate alone (25,26). The patterns of work outcomes for employed workers and homemakers were very similar in this study; combination treatment was superior to methotrexate for both absenteeism and presenteeism.…”
Section: Discussionsupporting
confidence: 84%
“…Treatment strategy trials have demonstrated that in the majority of patients with RA, the following approach is the most beneficial: goal-driven, dynamic treatment towards tight control of disease activity, including early introduction of one or more effective disease-modifying antirheumatic drugs (DMARDs) in combination with prednisone or anti-TNF, which includes tapering of the medication if remission or low disease activity is achieved (100). Currently, patients with RA tend to be treated first-line with a DMARD such as methotrexate (MTX) (15,16). Biologics are licensed for patients who show inadequate response or intolerance to DMARDs, and also for patients with severe, active, and progressive RA not previously treated with DMARDs (15).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…As such, the treatment of IMIDs overlaps, specifically in the management of severe disease. A developing body of data suggests that more aggressive therapeutic intervention earlier in the treatment pathway in RA and CD may provide high levels of efficacy and tolerability, with improved long-term patient outcomes and disease prognosis (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). No such early intervention studies have been carried out in psoriasis to date, although the possibility of modifying the course of the disease has been proposed (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Previous data on working capacity after introduction of biological treatment are conflicting. Some studies have reported a decrease in sick leave (24,25), while others found no significant effect on working capacity (26)(27)(28). Two recent studies reported a decrease in sick leave, but on the other hand, increasing disability pensions (29,30).…”
Section: Discussionmentioning
confidence: 99%